Pertanggungjawaban Hukum Pejabat Administrasi Negara Terhadap Keputusan Tata Usaha Negara Yang Dibatalkan Oleh Pengadilan Tata Usaha Negara. - Widya Hartati; Sandy Ari Wijaya; Salmi Yuniar Bahri (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Administrative Decisions (KTUN) are one of the important legal instruments issued by state administrative officials to carry out government functions. However, it is often found that KTUNs are legally defective due to violations of the principle of legality, general principles of good governance (AUPB), or applicable administrative procedures, which lead to their annulment by the State Administrative Court (PTUN). This study aims to analyze the legal basis and the form of legal responsibility in the administration of State Administrative Decisions (KTUN) that have been annulled. This research uses a juridical-normative method with an approach based on laws and regulations and legal doctrines. The study shows that the annulment of KTUNs by PTUN is usually caused by procedural and substantive violations, such as issuing decisions beyond authority or not meeting formal requirements. In the context of legal responsibility, the agency issuing the KTUN is obligated to retract the decision, restore the rights of the affected parties, and issue a new decision that complies with the law. Furthermore, the officials at fault may be subject to administrative sanctions, ranging from a warning to dismissal, depending on the severity of the error. State administrative officials whose KTUNs have been annulled must fulfill their legal responsibility by revoking or correcting the KTUN, restoring the rights of the affected parties, providing compensation, and implementing administrative sanctions if necessary. Additionally, criminal liability may apply if there is an element of abuse of power. This finding underscores the importance of compliance with the principles of AUPB and positive law in every administrative action to prevent harm to society.